A study of spontaneous narrative formation: coronavirus and narratives of doom. Issue 1 (2nd January 2023) - van den Berg-Cook, Nancy
Abstract : Is the frequently heard and seemingly innocent statement that the coronavirus was 'sent by Mother Nature to teach us a lesson, ' evidence of an unconscious narrative that is driven by the fear and grief engendered by the pandemic? The idiom 'teach us a lesson' suggests that Mother Earth is angry with us and further, that the archetype of divine punishment – apocalypse – has been activated in the collective unconscious. This may be a dangerous time for the world psyche because an archetype, as objective pattern as well as a 'dynamic living agency, ' can influence our emotions and behaviors . History has shown the devastation a powerfully activated negative archetype can engender. Can analytical psychology contribute to easing psychological suffering caused by the irrational fear of the end of the world? We suggest C.G Jung's 'transcendent function' can be invoked to spontaneously produce a new unifying, and therefore healing symbol.